AMPA receptor GluA2 subunit defects are a cause of neurodevelopmental disorders - Salpietro, Vincenzo; Dixon, Christine L.; Hacke, Moritz; Leib, Andreas (Nature Communications, 2019)
Genetic variants in ionotropic glutamate receptors have been implicated in neurodevelopmental disorders. Here, the authors report heterozygous de novo mutations in the GRIA2 gene in 28 individuals with intellectual disability and neurodevelopmental abnormalities associated with reduced Ca2+ transport and AMPAR currents.”
Gesehen am 26.08.2019